Peningkatan Daya Jual Dengan Pemasaran Berbasis Media Sosial - Fathimah, Vidya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2025)
The aim of this community service is to educate Rayyan Restaurant MSMEs (RM) about the importance of using social media in marketing products, so that the products can be known by the wider community, and can sell even better. The implementation method is that the lecturers at the SUKMA College of Management Sciences (STIM Sukma) survey MSMEs who are willing to be given education, then the lecturers create material to explain to MSME owners, then the lecturers explain the content of the material regarding product marketing via social media (Instagram and Whatsapp), then the final method is evaluation. The result of community service is the owner of RM MSMEs. Rayyan understood 100% of the explanation given by the STIM Sukma lecturer. And MSME owners will from time to time apply knowledge about product marketing via social media to increase sales.